Targeting of nuclear factor-kappaB and proteasome by dithiocarbamate complexes with metals - Cvek, B; Dvorak, Z (Current pharmaceutical design, 2007)
Dithiocarbamates and their complexes with transition metals have been used as common pesticides, vulcanizing or analytical agents for decades. These compounds are one of the most reported inhibitors of nuclear factor-kappaB (NF-kappaB) signaling cascade. Recently, it has been found that dithiocarbamates are very potent inhibitors of proteasome. NF-kappaB plays a central role in the immune system and is described as a major actor in many of human cancers mainly because of its protective effects against apoptosis. Molecular mechanisms involved in regulation and function of NF-kappaB pathway have been elucidated recently. In particular, pivotal zinc containing proteins that alter NF-kappaB signal transduction were recognized. Additionally, proteasome system was found to be a key player in NF-kappaB pathway and is an attractive target for anticancer drug development. Collectively, the capability of dithiocarbamates to inhibit NF-kappaB and proteasome makes these compounds promising anticancer agents. This review focuses on the biological activity of dithiocarbamate coordination compounds with regard to their possible molecular targets in NF-kappaB signaling and proteasome (JAMM domain proteins). Future research should aim to find the most suitable dithiocarbamate coordination compounds for treatment of cancer and other diseases.
Keywords: apoptóza; inhibitory proteasomu; Apoptosis; Metals; lidé; Antineoplastic Agents; protinádorové látky; signální transdukce; kovy; Signal Transduction; Proteasome Inhibitors; thiokarbamáty; proteasomový endopeptidasový komplex; Thiocarbamates; Ditiocarb; NF-kappa B; dithiokarb; Proteasome Endopeptidase Complex; Humans